The family rule: a reply to Alderson - Foreman, D M (1999)
In her commentary, Alderson makes four major criticisms of the family rule. She claims that: consent must be explicit; that consenting parties should be reasonably equal; that the concept of a family rule adds little to current understanding, and that the effect of applying the concept in practice will be to impair the consenting process. However, there are other important examples of implicit consent in daily life, and consent between unequals is common and unexceptionable. The family rule establishes an unequivocal ethical base for the role of children, parents and practitioners in the consenting process, which is sorely needed. This base structures practitioners' interventions towards children in an appropriately empowering manner. Therefore, Alderson's critical objections fail.